PERLINDUNGAN HUKUM BAGI BURUH DALAM KASUS PEMUTUSAN HUBUNGAN KERJA YANG TERTUNDA DI PT. ASCOT DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Gandana, Aan Tirta; Hendrayana, Agus; Dainsyah, Dainsyah; Dewi, Dian Amalia; Sidiq, Yudha Permana; Razak, A. Kamil; Kurniati, Yeti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study discusses the process of termination of employment (PHK) for reasons of retirement at PT Ascot and legal protection for the fulfillment of workers' rights based on the provisions of the applicable labor law in Indonesia. This study uses a normative juridical approach by examining laws and regulations such as Law Number 13 of 2003, Perppu on Job Creation, and Government Regulation Number 35 of 2021. The findings of the study show that the layoff process carried out by PT Ascot does not pay attention to the principle of fairness in compensation, where workers who have reached retirement age receive compensation that is equal to other workers. This is contrary to the positive legal provisions that give greater rewards to workers with long working periods. The study also emphasizes the importance of government oversight and the role of unions in ensuring the rights of retired workers. This study contributes to strengthening the legal protection of elderly workers and encouraging fair labor practices.